Pengembangan Variasi Model Latihan Sepakbola untuk Meningkatkan Taktik Penyerangan Sepakbola dengan Berbasis Jumlah Pemain - Hendra Jaya; Lusi Agelia; Mutia Muhardiyanti; Pani Suswari (Universitas Negeri Semarang, 2024)
The purpose of this study is to create a product based on a soccer attack tactic training model based on the number of players that are eligible for use. This research method used is the R&D method by Borg and Gall. The Targets of this study are coaches and athletes. This research developed the training models for attack strategy in soccer. The model used in this study is 12 player-based attack training models that have been adjusted to the model's difficulty level. In the Design product result and percentage assessment in this study, media experts are in the feasible category at 98.67%, and material experts are in the very good/very feasible category at 87.27%. The study of 12 player-based attack tactic training models concludes that it is feasible to use and effective in improving attack tactic abilities. Research recommendations are that athletes use this reference as an alternative for training, while coaches as an alternative media in the training process are more interesting and effective. Variations in Football Training Models in improving football attack tactics further research has more training models than the current one